2022
DOI: 10.18632/aging.204249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BBT-877, a novel inhibitor of ATX, on a mouse model of type 1 diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is one of the common microvascular complications of diabetes. Autotaxin (ATX) is an enzyme with lysophospholipase D activity, producing lysophosphatidic acid (LPA). LPA signaling has been implicated in renal fibrosis, thereby inducing renal dysfunction. BBT-877 is an orally administered small molecule inhibitor of ATX. However, its effect on DN has not been studied so far. In this study, we investigated the effect of BBT-877, a novel inhibitor of ATX, on the pathogenesis of DN in a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Hyperglycemia can change podocyte phenotype by inducing the loss of nephrin, altering the production/degradation of extracellular matrix components, and enhancing pro-trophic cytokine-modifying growth factors [ 28 ]. However, LPA has been recently identified as another important factor in DN pathogenesis [ 12 , 13 , 14 , 15 ]. Zhang et al reported that LPAR1/3 inhibition in type 2 diabetic mice restored podocyte marker expression and the podocyte number in glomeruli [ 15 ]; however, the underlying mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperglycemia can change podocyte phenotype by inducing the loss of nephrin, altering the production/degradation of extracellular matrix components, and enhancing pro-trophic cytokine-modifying growth factors [ 28 ]. However, LPA has been recently identified as another important factor in DN pathogenesis [ 12 , 13 , 14 , 15 ]. Zhang et al reported that LPAR1/3 inhibition in type 2 diabetic mice restored podocyte marker expression and the podocyte number in glomeruli [ 15 ]; however, the underlying mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with diabetes experiencing DN had significantly enhanced urinary levels of LPA and LPC when compared with patients without DN [ 11 ]. Additionally, several previous studies, including by our research group, have shown that inhibition of LPA signaling can attenuate DN-associated fibrosis and renal inflammation in diabetic animal models [ 12 , 13 , 14 , 15 ]. Although the antagonism of LPAR1/3 protects against podocyte loss in endothelial nitric oxide synthase (eNOS) −/− db/db mice, a type 2 diabetes model [ 15 ], the role of LPA/LPAR1 signaling in podocyte damage during DN remains unexplored.…”
Section: Introductionmentioning
confidence: 98%
“…Diabetes was induced by intraperitoneal (i.p.) injections of STZ (Aladdin, Shanghai, China) at a dose of 50 mg/kg for 5 consecutive days, as previously described ( Lee et al, 2022 ; Song et al, 2022 ; Zhong et al, 2019 ). Mice with blood glucose >16.7 mmol/L were considered diabetic 3 days after the injection ( He et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…One of the hallmarks of DN is the progressive expansion of the mesangial matrix, which is developed by the accumulation of the components of the extracellular matrix (ECM) [5]. Alteration in local gene expression of humoral growth factors, such as transforming growth factor-β (TGF-β), connective tissue growth factor (CTGF), and platelet-derived growth factor (PDGF), may promote elevated production of the ECM component, e.g., fibronectin and collagen IV, or decreased degradation by matrix metalloproteinases, e.g., MMP-1 and MMP-2, in DN [6][7][8].…”
Section: Introduction 1diabetic Nephropathymentioning
confidence: 99%